Targums and the transmission of scripture into Judaism and Christianity - Hayward, Robert, 1948- (Leiden ; Boston : Brill, 2010)
This collection of seventeen previously published essays and two hitherto unpublished articles examines strategies adopted by ancient Aramaic translators of the Hebrew Bible in their attempts to transmit the meaning of Scripture to their own generations. The intricate interpretations of Targum Pseudo-Jonathan feature prominently: analysis of them suggests a date for the substance of this Targum rather earlier than is commonly assumed. The biblical exegesis of Jerome (ca. 342-420 CE) often reflects Targumic interpretation of Scripture: as well as helping to date items of Jewish interpretation.
Acknowledgements; Preface; Abbreviations; PART ONE TARGUMIC PORTRAYALS OF BIBLICAL FIGURES; I. Shem, Melchizedek, and Concern with Christianity in the Pentateuchal Targumim; II. Abraham as Proselytizer at Beer-sheba in the Targums of the Pentateuch; III. Balaam's Prophecies as Interpreted by Philo and the Aramaic Targums of the Pentateuch; IV. The Figure of Adam in Pseudo-Philo's Biblical Antiquities; V. The Sacrifice of Isaac and Jewish Polemic against Christianity; VI. A Portrait of the Wicked Esau in the Targum of Codex Neofiti 1; PART TWO DATING TARGUM PSEUDO-JONATHAN.
Includes bibliographical references and indexes.
Print version record.
Master record variable field(s) change: 630, 650
Keywords: Bible. -- Criticism, interpretation, etc; Midrash; Bible; Targum; Targum Jeruschalmi I; Hieronymus, Sophronius Eusebius; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Church history -- Primitive and early church, ca. 30-600; Rabbinical literature -- History and criticism; RELIGION -- Judaism -- Sacred Writings; RELIGION -- Biblical Studies -- Old Testament; Church history -- Primitive and early church; Judaism -- Post-exilic period (Judaism); Rabbinical literature; Datierung; 586 B.C. - 600 A.D.; Electronic books; Criticism, interpretation, etc; History